Comparative Study of Intramedullary Interlocking Nailing and Minimally Invasive Percutaneous Plate Osteosynthesis for Distal Tibia Extra-Articular Fractures (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Management of distal tibial extra-articular fractures presents a significant challenge in orthopedic practice due to their complex anatomical features and variable fracture patterns. Surgical intervention plays a crucial role in achieving stable fixation and optimal functional outcomes. This study aimed to compare the effectiveness between minimally invasive percutaneous plate osteosynthesis and intramedullary nailing for the management of distal tibial extra-articular fractures. This was a prospective observational study that was conducted in the Department of Orthopedics, Bangabandhu Sheikh Mujib Medical College, Hospital (BSMMCH), Faridpur, Bangladesh from January 2021 to December 2022. Total 24 patients having a fracture of the distal third of the tibia were enrolled in this study as the study subjects. Total patients were divided into two groups. In group A, 12 patients underwent minimally invasive percutaneous plate osteosynthesis (MIPPO) and in group B, 12 patients underwent intramedullary nailing (IMN). A random selection method was used in sample selection. According to Olerud Molander’s score, Excellent, Good and Fair results were found in 50%, 50%, and 0% of the group A patients respectively. On the other hand, those results were found in 42%, 50% and 8% of group B patients respectively. Although both minimally invasive percutaneous plate osteosynthesis and intramedullary nailing procedures are effective in managing distal tibial extra-articular fractures, considering excellent union rate, low blood loss and remarkable Olerud Molander’s score, MIPPO may be considered as the better option.Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):92-96.